2011
DOI: 10.1002/ejic.201001356
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Homoleptic and Heteroleptic Cobalt, Nickel, Copper, Zinc and Cadmium Compounds with the 2‐(Tosylamino)‐N‐[2‐(tosylamino)benzylidene]aniline Ligand

Abstract: The electrochemical oxidation of anodic metal (cobalt, nickel, copper, zinc and cadmium)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 75 publications
2
5
0
Order By: Relevance
“…The calculated distances between the two Ni(II) centres and the sulfonyl oxygens lie between 2.096 Å and 2.224 Å. Reported values of this structural motif are in the range of 2.09 44 to 2.43 Å 46 , hence the computations are in line with experimental precedence.…”
Section: Dalton Transactions Accepted Manuscriptsupporting
confidence: 77%
See 1 more Smart Citation
“…The calculated distances between the two Ni(II) centres and the sulfonyl oxygens lie between 2.096 Å and 2.224 Å. Reported values of this structural motif are in the range of 2.09 44 to 2.43 Å 46 , hence the computations are in line with experimental precedence.…”
Section: Dalton Transactions Accepted Manuscriptsupporting
confidence: 77%
“…This is justified by experimental data of a number of structurally characterized Ni(II) complexes where sulfonamido groups act as bidentate donors via N,O coordination. [44][45][46] Starting from a sixcoordinate geometry in which the sulfonyl oxygen atoms act as axial donors, an optimum geometry was found (Table S3 ‡). Consequently, the geometry around the Ni(II) centre is a slightly distorted octahedron.…”
Section: Paper Dalton Transactionsmentioning
confidence: 99%
“…The stacking interactions are mainly connected with aromatic molecules, [1][2][3][4][5][6][7][8][9][10] however it was shown that various rings can form stacking interactions; aliphatic saturated [11][12][13][14][15][16] and unsaturated molecules, 17,18 metal-chelate rings, [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] and hydrogen-bridged rings. [39][40][41][42] 2D materials can also form stacking interactions.…”
Section: Introductionmentioning
confidence: 99%
“…Stretching vibrations of the imino group in 2-N-tosylaminobenzaldehyde azomethines are typically observed at 1600-1630 cm −1 and they do not shift significantly upon complex formation [16,[61][62][63]. The spectral changes observed are consistent with the deprotonation and direct involvement of the tosylamino group into the metal binding.…”
Section: Spectroscopic Propertiesmentioning
confidence: 57%